KEDUDUKKAN ASHABAH DALAM KASUS ‘AUL MENURUT IBNU ABBAS - Fitriyati, Yusida (Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract: Residuary heirs are groups that are not specified portion size. The impact of this provision, there is no residuary get the final after being given to the heirs ashab furudh. Case ‘aul accords to Ibn Abbas because when there is no shortage of treasures then ashab furudh impure group that will be shared at the end. Ashabul impure furudh this is a group that on other occasions either be a residuary. This article wants to know the position of the case of a residuary 'aul according to Ibn Abbas and investigated the reasons of the opinion of him.ملخص: ورثة تكميلي هي المجموعات التي لا يتم تحديد حجم الجزء. تأثير هذا الحكم، وليس هناك تكميلي الحصول نهائي بعد أن تقدم لبقية الورثة الأشهب. القضية وفقا لابن عباس لأنه عندما لا يكون هناك نقص في الكنوز ثم المجموعة الأشهب نجس بقية من شأنها أن تكون مشتركة في نهاية المطاف. الصحابة من بقية هذه ليست مجموعة نقية في أوقات أخرى يكون راحة جيدة تكميلي ريث دون أصدقاء وبقية هناك أصدقاء. الكتابة هي معرفة موقف في حالة تكميلي المتبقية وفقا لابن عباس والتحقيق في أسباب رأي ابن عباس.Kata Kunci: Ashabah, ‘Aul